A case of Crimean-Congo haemorrhagic fever imported in Greece: Contact tracing and management of exposed healthcare workers. Issue 4 (July 2019) - Maltezou, Helena C; Papa, Anna; Ventouri, Sarantoula; Tseki, Charikleia; Pervanidou, Danai; Pavli, Androula; Panagopoulos, Periklis; Markatou, Philothei; Gavana, Elpida; Maltezos, Efstratios
Background: Nosocomial transmission is a major mode of infection of Crimean-Congo haemorrhagic fever (CCHF). In May 2018, a patient with CCHF was hospitalised in Greece. Objective: Our aim was to present the management of healthcare workers (HCWs) to the CCHF case. Methods: Contact tracing, risk assessment and follow-up of exposed HCWs were performed. Testing (RT-PCR and/or serology) was offered to contacts. Post-exposure prophylaxis (PEP) with ribavirin was considered for high-risk exposures. Results: Ninety-one HCWs were exposed to the case. Sixty-six HCWs were grouped as high-risk exposures. Ribavirin PEP was offered to 29 HCWs; seven agreed to receive prophylaxis. Forty-one HCWs were tested for CCHF infection; none was found positive. Gaps in infection control occurred. Discussion: CCHF should be considered in patients with compatible travel history and clinical and laboratory findings. Early clinical suspicion and laboratory confirmation are imperative for the implementation of appropriate infection control measures. Ribavirin should be considered for high-risk exposures. Infection control capacity for highly pathogenic agents should increase.